Age-Related Changes of Sprint Kinematics - Dahl, Julian; Degens, Hans; Hildebrand, Frank; Ganse, Bergita (Frontiers in Physiology, 2019)
The sprint performance of master athletes decreases with age, but little is known about possible contributions of changes in sprint kinematics. The aim of this study was to assess the influence of age, sex and sprinting kinematics on sprint performance. To investigate this, 199 men (30-89 y) and 81 women (33-76 y), bending over, brake, propulsion, leg stiffness and hip flexion angles were assessed during a sprint stride using high-resolution video analyses. Propulsion angle (men 25 ± 4.2, women 23.7 ± 4) was larger and hip flexion angle (men 25.3 ± 7.3, women 28 ± 5.7) smaller in men than women (both p < .001). Bending over angle (p = .004), brake angle (p = .004) and hip flexion angle (p < .001) increased, propulsion angle (p < .001) and leg stiffness angle (p = .001) decreased with age, irrespective of sex. While performance was mainly determined by age (R2 = .501, p < .001) and sex (adjusted R2 = .642), hip flexion angle (adjusted R2 = .686) and bending over angle (adjusted R2 = .705) contributed also to performance in 60-m sprints. In 200-m sprints in addition to age and sex only hip flexion angle (age R2 = .506; age + sex adjusted R2 = 641; age + sex + hip flexion adjusted R2 = .655) contributed to performance. In conclusion, the kinematics of sprinting differ between sexes and change with age. The ageing-related changes of sprinting have a minor contribution to the ageing-related decline in performance